L’enseignement du cinéma dans le Précis d’initiation au cinéma (Agel H. et G., 1956) - Pascal Laborderie (Mise au Point)
The aim of this article is to study the Précis d'initiation au Cinéma (The Handbook of cinema), which focuses on the teaching of cinema in French schools. Henri Agel, the author, is amongst the first who introduced cinema teaching in secondary schools. The Précis d'initiation au Cinéma, co-written with his wife Geneviève, was the first introductory manual to film language for secondary level teaching. For this reason, it is important to investigate the educational and ideological choices of this book to gain a proper understanding of the development of film studies and Catholic cinephilia. In order to show the emergence of one of the major approaches to teaching film studies in France, we will examine three strands in the Précis d’initiation au cinéma: historical, didactic and ideological.